Apigenin ameliorates imiquimod-induced psoriasis in C57BL/6J mice by inactivating STAT3 and NF-κB - Xianshe Meng; Shihong Zheng; Zequn Yin; Xuerui Wang; Daigang Yang; Tingfeng Zou; Huaxin Li; Yuanli Chen; Chenzhong Liao; Zhouling Xie; Xiaodong Fan; Jihong Han; et al. (Food Science and Human Wellness)
Psoriasis is a chronic autoimmune disease featured by patches on the skin. It is caused by malfunction of immune cells and keratinocytes with inflammation as one of its key features. Apigenin (API) is a natural flavonoid with anti-inflammatory and immunoregulatory properties. Therefore, we speculated that API can ameliorate psoriasis, and determined its effect on the development of psoriasis by using imiquimod (IMQ)-induced psoriasis mouse model. Our results showed that API attenuated IMQ-induced phenotypic changes, such as erythema, scaling and epidermal thickening, and improved splenic hyperplasia. Abnormal differentiation of immune cells was restored in API-treated mice. Mechanistically, we revealed that API is a key regulator of signal transducer activator of transcription 3 (STAT3). API regulated immune responses by reducing interleukin-23 (IL-23)/STAT3/IL-17A axis. Moreover, it suppressed IMQ-caused cell hyperproliferation by inactivating STAT3 through regulation of extracellular signal-regulated kinase 1/2 and nuclear factor-κB (NF-κB) pathway. Furthermore, API reduced expression of inflammatory cytokines through inactivation of NF-κB. Taken together, our study demonstrates that API can ameliorate psoriasis and may be considered as a strategy for psoriasis treatment.